Early results of a simplified protocol over standard in patients undergoing transcatheter aortic-valve replacement. (3rd October 2022) - Tamargo, M; Garcia-Carreno, J; Gutierrez, E; Vazquez, M E; Sanz-Ruiz, R; Diez-Delhoyo, F; Blazquez, Z; Castrodeza, J; Soriano, J; Alonso, A; Zatarain, E; Arenal, A; et al.
Abstract: Introduction: Transcatheter aortic-valve replacement (TAVR) procedure has been simplified, being now a less-invasive minimalist strategy the standard of treatment. Therefore, length of hospitalization has decreased, and early-discharge (ED) (<72 hour) protocols are in development. Lately, additional techniques to optimize TAVR procedure have arisen, such as the use of radial approach as the secondary access, conscious sedation, cusp overlap projection (COP) to better control the implantation depth in self-expanding (SE) valves, or atrial pacing (AP) after deployment to test atrioventricular (AV) conduction. With the combination of these 4 maneuvers, we have developed an ED protocol, and hereby present the immediate results. Methods: We prospectively studied 176 patients who underwent staged and transfemoral TAVR procedure with our novel protocol between May 2020 and December 2021 (Protocol) and compared them with a retrospective cohort of 175 patients who underwent standard TAVR between January 2018 and April 2020 (Standard). The protocol cohort included the use of conscious sedation with midazolam and fentanyl, routine radial approach as the secondary access, use of the CO projection, and AP after deployment in the absence of complete AV block, at rates of 70 to 120 beats/min (or until AV Block was observed) in 10 beats/min increments for a total of 20 beats at each increment. As part of this protocol, patients remained in general cardiology ward, avoiding ICU stay, with rapid recovery and early mobilization (After 6 hours in the absence of bleeding). In the absence of complications patients were discharged within 24–48 hours and reviewed a week and a month later in clinic. Initial assessment included EKG, echocardiogram, in hospital and 30-day follow-up. Results: Median patient age was 80 years old and 49.9% were female. Despite higher rates of hypertension in the standard cohort (p=0.038), no significant differences could be appreciated in baseline demographics, EKG or imaging findings (Table). Even with higher rates of predilation, CO and AP, the length of procedure and the use of contrast was lower in the protocol cohort. Rates of intraprocedural AV block were similar among groups (p=p.21), but AP led to a significant lower need of temporary pacemaker surveillance (p<0.0001). The use of radial access also tend to diminish immediate bleeding and vascular complications. According to protocol, the median length of stay was reduced to 2 [1; 4] days (p<0.0001). At a 30-day follow up, the incidence of major adverse cardiac events was low and similar among groups (p=0.67) (Figure), with no significant differences in the incidence of permanent pacemaker implantation, heart failure admission, bleeding o vascular complication (Figure) Conclusion: A simplified TAVR protocol combining radial access, CO, AP can be adopted safely, leading to TAVR patients early discharge, with no major events on an immediate 30-day follow-up. Funding Acknowledgement: Type of funding sources: None.